X-ray Characteristics of NGC 3516: A View through the Complex Absorber - Turner, T; Miller, L; Kraemer, S; Reeves, J (2011)
We consider new Suzaku data for NGC 3516 taken during 2009, along with other recent X-ray observations of the source. The cumulative characteristics of NGC 3516 cannot be explained without invoking changes in the line-of-sight absorption. Contrary to many other well-studied Seyfert galaxies, NGC 3516 does not show a positive lag of hard X-ray photons relative to soft photons over the timescales sampled. In the context of reverberation models for the X-ray lags, the lack of such a signal in NGC 3516 is consistent with flux variations being dominated by absorption changes. The lack of any reverberation signal in such a highly variable source disfavors intrinsic continuum variability in this case. Instead, the colorless flux variations observed at high flux states for NGC 3516 are suggested to be a consequence of Compton-thick clumps of gas crossing the line-of-sight.